Measuring entrepreneurial activity in low-teledensity countries. (1st January 2011) - Frederick, Howard; Haslett, Stephen; Wolfgramm, Tania; Finau, 'Ata'ata
In 2009, a team of 38 researchers carried out the Global Entrepreneurship Monitor (GEM) survey of social and business entrepreneurial activity in the Kingdom of Tonga. The GEM survey estimates the proportion of the population involved in business and social start-ups and new firm creation. This paper describes not the results of the survey but rather the methodology employed. Because Tonga is spread out over a swath of the Pacific Ocean, the team faced challenges in terms of survey design, field work, logistics, and quality control. To meet the standards of rigour, we designed a 'ruggedised method' for measuring entrepreneurial activity. Countries with a teledensity threshold of less than 30% (fixed lines per 100 inhabitants) present serious challenges to survey designers. The study discusses questionnaire preparation, recruitment and training of interviewers as well as survey design issues such as sample size, response rate, sampling weights, and lessons learned. The report will assist other teams in measuring entrepreneurial activity in low-teledensity countries and provides guidelines when the study is repeated elsewhere. The study also proposes a way forward to incorporate new technologies such as tablet PCs, GPS, and GIS to address the dilemmas of measuring entrepreneurial activity in low-teledensity countries.